The Influence of Company Size, Financial Leverage, Cash Holding and Managerial Ownership on Income Smoothing - Prasasti, Yuli Candra; Febyansyah, Andar (PT Inovasi Pratama Internasional, 2024)
This research aims to analyze the influence of company size, financial leverage, cash holding and managerial ownership on income smoothing in food and beverage companies. The research method used is quantitative from financial report data listed on the Indonesia Stock Exchange (BEI) with a population of 90 samples from 18 companies. The results of data analysis show that there is a positive correlation between company size and cash holding, but the results from financial leverage and managerial ownership show a negative correlation. The implications of this research can be an evaluation material for companies and investors and provide additional information regarding what factors influence income smoothing.